Correlation of the stature with arch and chord dimensions in young subjects using carrea's index- An anthropometric study - Kumar Anand; Neal B Kedia; Neha Kumari; Vishal Kumar; Khushboo Rani; Prerna Soni (Wolters Kluwer Medknow Publications, 2023)
Background: Forensic identifications have utilized the height or stature of an individual in their field. Teeth and dentition can act as reliable tools to estimate the stature in cases where the only skull is presented as evidence. The Carrea's index assesses the stature in a subject from the lower anterior teeth dimensions. Aim: The present study was aimed to judge the reliability of Carrea's index in Indian subjects. Materials and Methods: From 80 subjects who were undergraduate students, plaster models were made and each was assessed individually making 160 hemiarches. These hemiarches were divided based on the teeth alignment into normal, diastema, and crowded forms. This was followed by measurement with a vernier caliper into chord and arch. Results: In both genders, the difference seen was statistically significant between dental arch types concerning various alignments with 95.23% and 83.75% success for males and females in normal dentition and 92.30% and 85.71% in crowded dentition. Also, a significant difference was seen for the type of arch with P ≤ 0.001 and 0.003, respectively. Lesser success was seen for spacing in both the genders and arches. Conclusion: The present study concludes that Carrea's index is a dependable and efficient tool for estimating height in subjects having arches with crowded and normal dentition which is functional for both the gender on the left and right side of the dental arches. However, in hemiarches with diastema, this method is not reliable.